Rapid reversal of diffuse cerebral edema with correction of serum sodium in acute water intoxication. (August 2020) - Austin, Adam; Saha, Biplab K.; Giampa, Joseph; Beegle, Scott H.
Highlights: Acute Water Intoxication (AWI) can manifest with nausea, headache, seizure, coma and death. AWI should be in the differential for diffuse cerebral edema. Reversal of cerebral edema due to AWI can be accomplished with appropriate management of hyponatremia. Abstract: Acute water intoxication (AWI) is a disorder of excess water intake that can manifest in neurological injury and death. We describe a case of a 54-year-old man that presents to the emergency department with a generalized toxic-clonic seizure due to AWI. Initial computed tomography of the brain demonstrated diffuse cerebral edema. However, with correction of serum sodium over the one hospital day, the patient's neurological symptoms and imaging completely resolved. Clinicians should recognize of reversibility of this entity with management of hyponatremia.